The impact of source credibility on Saudi consumer’s attitude toward print advertisement: the moderating role of brand familiarity / Methaq Ahmed Abdulmajid - Abdulmajid, Methaq Ahmed (Universiti Teknologi MARA, Perlis, 2011)
An endorser or a spokesperson is frequently used by marketers in their product advertisements as a credible source that is hoped to influence the attitude of consumers in the marketplace toward the shown advertisement, the brand and most importantly their purchase intentions. Corporate credibility C/C – the reputation of a company for honesty and expertise is another type of source credibility that is said to influence consumers’ reaction to the shown product advertisements and shape their attitudes to brands. The present study assessed the impact of both source credibility (corporate credibility (C/C) and endorser credibility En/C) on Saudi consumers’ attitude toward advertising (Aad), attitude toward brand (Ab), and purchase intention (PI) when brand familiarity is tested. A study carried out in Saudi Arabia using 150 respondents as consumers who used cover head product of (AL-Bassam). Path analysis confirmed that, attractiveness of endorser had strengthened impact on (Aad), then expertise, while no effect for endorser trustworthiness on (Aad). While trustworthiness is significant in all C/C relations with the other variables (i.e. Aad, Ab and PI), there is no effect for PAB on relationship between (Aad) and (Ab). In this study, the said relationships amongst the six variables are revisited. The difference lie in the use of Saudi consumers, a developing country compared to developed countries in past studies, in addition to the use of a real advertisement including (product, endorser and company) rather than make believe advertisement. This will provide the first insight on Saudi consumer’s behavior.